2019
DOI: 10.1002/chem.201903706
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Characterization of a Pair of Isomers of Heteroleptic Bis(Bidentate) Ruthenium(II) Complexes with Two Different Monodentate Ligands

Abstract: Twoi somerso fh eteroleptic bis(bidentate) ruthenium(II) complexes with dimethyl sulfoxide (dmso) and chloride ligands, trans(Cl,N bpy )-and trans(Cl,N Hdpa )-[Ru(bpy)Cl-(dmso-S)(Hdpa)] + (bpy:2 ,2'-bipyridine;H dpa:d i-2-pyridylamine), are synthesized. This is the first reporto nt he selective synthesis of ap air of isomers of cis-[Ru(L)(L')XY] n + (L ¼ 6 L':bidentate ligands;X¼ 6 Y: monodentate ligands). The structures of the ruthenium(II) complexes are clarified by means of X-ray crystallography,a nd the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Both angles were consistent with those of the Hdpa ligand in previously reported Ru(II)-Hdpa complexes (25.9-48.2 ). 18,29,39,40 The difference between the two dihedral angles is likely caused by steric interactions between H 2 pia and the two Hdpa ligands. The N2 atom of the NH group in Hdpa(N1,N3) established contact with the O1 atom of H 2 pia (N2/O1 ¼ 3.036 Å; Fig.…”
Section: Crystal Structures Of Synthesized Chloride and Uoride Saltsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both angles were consistent with those of the Hdpa ligand in previously reported Ru(II)-Hdpa complexes (25.9-48.2 ). 18,29,39,40 The difference between the two dihedral angles is likely caused by steric interactions between H 2 pia and the two Hdpa ligands. The N2 atom of the NH group in Hdpa(N1,N3) established contact with the O1 atom of H 2 pia (N2/O1 ¼ 3.036 Å; Fig.…”
Section: Crystal Structures Of Synthesized Chloride and Uoride Saltsmentioning
confidence: 99%
“…Moreover, the dihedral angle for the other Hdpa(N4,N6) was signicantly smaller than that in the chloride salt (15.8 and 29.9 , respectively), and smaller than previously reported Ru(II)-Hdpa data (25.9 -48.2 ). 18,29,39,40 Generally, the bent conformation of Hdpa cuts off a p-conjugated system between two pyridyl groups in the Hdpa ligand. However, the smaller dihedral angle of Hdpa(N4,N6) indicated that this Hdpa possessed the p-conjugated system of the entire Hdpa ligand, similar to a coordinated bpy ligand.…”
Section: Crystal Structures Of Synthesized Chloride and Uoride Saltsmentioning
confidence: 99%